PENGENDALIAN RESPIRASI UNTUK MEMPERTAHANKAN MUTU PASCA PANEN PRODUK SEGAR HORTIKULTURA - Sutrisno . (PERTETA, 2007)
ABSTRACTThe Public demand on fresh horticultural products is fairly high, and the data showed for the past few years, the domestic and overseas demands for fresh (topical fruits have a tandency to incrase. Fresh horticultural are perishable ptoduces with limited of shelf life. Consequently, the continuity of fruit supply could be distrubed in terms of time, quantity, and quality. On the order hand, the moden market need the perpect delivery and want the fruits in the consumer hands in fresh, uniformly ripened, and ready to consume conditions. Biological products still carry out metabolic activity like respiration even after harvest, Most of the postharvest physico-chemical canges of frutis are related to respiration, such as maturity process, developmentof aroma and sweetness, softening of fruit meat, quality degradiation, etc. Thus, controlling the respiration process could be done for maintaining the qualityof fruits during post-hervest handling. Over the past years, the mathematical model for predicting and thus controlling respiration characteristics were already developed by many researchers. An application of the results of those research were also commercially used such as for Cold Storage, Modified Atmosphere Packaging (MAP), Artifical Ripening (AR) and Controlled Atmosphere Storage (CAS). This paper will reviewed the importance of controlling the respiration in relation to perserved the quality of fresh horticultural products during post-harvest handling. Keyword: respiration, Modified Atmosphere Packaging/ MAP, Controlled Atmosphere Storage/ CAS, Cold Storage, Shelf life Diterima: 11 Juli 2007; Disetujui: 31 Agustus 2007